Phytosome Based Drug Delivery of Naringenin and Naringin: Development, Characterization, and In Vivo Evaluation - Prince Modi,; P.K. Choudhury,; Maya Sharma, (Asian Journal of Pharmaceutical Research and Development, 2025)
Phytosomes represent a modern approach to enhancing the oral bioavailability and therapeutic efficacy of poorly soluble plant-derived compounds. This comprehensive study details the development, physicochemical characterization, and in vivo evaluation of phytosome formulations of two significant citrus flavonoids, naringenin (NGN) and naringin (NRN). Despite their potent pharmacological activities, both NGN and NRN face challenges related to low aqueous solubility, poor oral absorption, and extensive first-pass metabolism, which severely limit their clinical application. Phytosomes of NGN and NRN were prepared using the rotary evaporation method, and the process was optimized using a Box–Behnken Design (BBD) to achieve high product yield and entrapment efficiency. The optimized formulations were subjected to extensive characterization, including particle size analysis, zeta potential measurement, and morphological and structural analysis using TEM, FTIR, and DSC. In vitro release studies demonstrated a significant increase in drug dissolution from the phytosome formulations compared to the free drugs. A subsequent in vivo pharmacokinetic study in rabbits confirmed that the phytosome formulations exhibited a marked increase in plasma drug concentration and enhanced bioavailability. These findings collectively demonstrate that phytosome technology is a highly effective drug delivery system for overcoming the pharmacokinetic limitations of these flavonoids and holds significant promise for their future therapeutic application.